2015
DOI: 10.1002/ece3.1440
|View full text |Cite
|
Sign up to set email alerts
|

Landscape‐scale accessibility of livestock to tigers: implications of spatial grain for modeling predation risk to mitigate human–carnivore conflict

Abstract: Innovative conservation tools are greatly needed to reduce livelihood losses and wildlife declines resulting from human–carnivore conflict. Spatial risk modeling is an emerging method for assessing the spatial patterns of predator–prey interactions, with applications for mitigating carnivore attacks on livestock. Large carnivores that ambush prey attack and kill over small areas, requiring models at fine spatial grains to predict livestock depredation hot spots. To detect the best resolution for predicting whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 52 publications
(138 reference statements)
3
80
1
Order By: Relevance
“…The locations of these sites were determined by generating random points stratified across a 200-m grid in ArcGIS, with one point per pixel separated by at least 200 m so as not to repeatedly sample the same area. While ground-surveying these random sites for another study (Miller et al 2015), no wild or domestic prey carcasses were observed.…”
Section: Landscape Attributesmentioning
confidence: 98%
See 3 more Smart Citations
“…The locations of these sites were determined by generating random points stratified across a 200-m grid in ArcGIS, with one point per pixel separated by at least 200 m so as not to repeatedly sample the same area. While ground-surveying these random sites for another study (Miller et al 2015), no wild or domestic prey carcasses were observed.…”
Section: Landscape Attributesmentioning
confidence: 98%
“…To obtain more detailed spatial, temporal, and demographic data on the livestock killed, we conducted ground surveys of freshly killed livestock reported for compensation from December 2011 through August 2012. Sampling methods are described in detail in Miller et al (2015) and overviewed here.…”
Section: Data Collection At Livestock Kill Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, large carnivores also pose many real and perceived threats to people and communities that live within carnivore home ranges. Carnivores can kill livestock and pets (e.g., Naughton- Treves et al 2003, Morehouse and Boyce 2011, Miller et al 2015, cause property damage (e.g., Wilson et al 2006, Treves 2009), affect cattle weight gain (Ramler et al 2014), and pose a risk to human safety (e.g., Treves andNaughton-Treves 1999, Ratnayeke et al 2014). Although separating people and carnivores at small scales, e.g., exclusion from calving pastures or yard sites, often is desirable, the separation model is unrealistic at larger scales where there is not enough space for carnivores if they are restricted from humansettled lands (e.g., Woodroffe andGinsberg 1998, Chapron et al 2014).…”
Section: Introductionmentioning
confidence: 99%